2001
DOI: 10.3386/w8198
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Happiness: Are Europeans and Americans Different?

Abstract: We study the effect of the level of inequality in society on individual well being using a total of 123,668 answers to a survey question about "happiness". We find that individuals have a lower tendency to report themselves happy when inequality is high, even after controlling for individual income, a large set of personal characteristics, and year and country (or, in the case of the US, state) dummies. The effect, however, appears to be stronger in Europe than in the US. In addition we find a striking differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
455
1
16

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(506 citation statements)
references
References 0 publications
33
455
1
16
Order By: Relevance
“…The results suggest that a one-standard-deviation increase in a worker's own wage would lead to an increase in happiness of 0.13 standard deviations. This finding is reminiscent of the conclusion by Alesina et al (2004) that "money buys happiness." Given that the impact of absolute wages on subjective well-being is stronger than that of relative wages, an across-the-board wage hike of, say, 10 percent would be associated with an overall increase in reported happiness.…”
Section: Resultssupporting
confidence: 55%
“…The results suggest that a one-standard-deviation increase in a worker's own wage would lead to an increase in happiness of 0.13 standard deviations. This finding is reminiscent of the conclusion by Alesina et al (2004) that "money buys happiness." Given that the impact of absolute wages on subjective well-being is stronger than that of relative wages, an across-the-board wage hike of, say, 10 percent would be associated with an overall increase in reported happiness.…”
Section: Resultssupporting
confidence: 55%
“…This is in line with Hirschman & Rothschild (1973) It should be noted that while we use the median of the income distribution in respondents' geographic areas as reference income, there is no reason to assume that only the first moment of the distribution is related to well-being. A substantial literature concerns the relationship between income inequality and SWB (e.g., Alesina et al, 2004;Graham & Felton, 2006;Oishi et al, 2011;Van Praag & Ferrer-i-Carbonell, 2009). While it is shown in Section 5.5 that the baseline results hold controlling for ZIPcode and MSA Gini coefficients, the current paper does not present a thorough analysis of the income-inequality-SWB relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Most past research has concluded that relative deprivation, or inequality, will lead to lower happiness. Alesina et al (2004) found that the poor in America faced with income inequality do not report high happiness scores, whereas inequality reduces happiness in Europe, especially for those with leftist views. Both McBride (1998) andLuttmer (2005) find a between-group inequality in nature, and it is regarded as a more influential element than "vertical inequality" (for example, income Gini coefficient) in determining social conflicts and long-term growth (Stewart, 2001;Stewart et al, 2005;Stewart and Langer, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%